Utilisation of InSAR for subsidence monitoring over the caving zone of underground metalliferous mine - Jarosz, Andrew; Zahiri, Hani; Warren, M.; Sowter, A. (European Space Agency, 2007)
The utilisation of InSAR techniques for the monitoring of surface subsidence over mining areas, employing open pit and underground mining methods, has a large potential due to accessibility and safety issues associated with the usage of classical surveying techniques. InSAR can also be very competitive concerning the cost of provided results. However, there are a few issues that may significantly limit InSAR applicability for subsidence monitoring in mining areas; particularly, the highly dynamic character ofsubsidence induced by mining, specially caving as an extraction method. The high rate of subsidence with relation to the frequency of SAR acquisitions may lead to an ambiguity issue. This could happen when the vertical movement between the neighbouring cells (pixels) of the SAR image is greater than half of the wavelength of a radar signal. The altered terrain topography, involving steep slopes and deep pits, may also lead to radar signal overlay issues for specific satellite and pit slope geometry.In this paper the authors analyse the above-mentioned issues and present how the InSAR technology was applied as a help to monitor large scale and highly dynamic subsidence for real case study in Western Australia. By combining the InSAR results with othersurveying techniques (GPS, slope stability monitoring system and topographic surveys) a comprehensive model of surface deformation was created. It was also recognised that the analysis of ground deformation dynamics, based on topographical surveys, may provide a basis for the resolution of ambiguity issues existing in InSAR processing. The overall objective of this project was to provide help with tuning the finite element model and analysis required for planning and design of the next mining phase.